2020
DOI: 10.1016/j.jpcs.2019.109322
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of low-dimension MSe2(M = Ti, Hf, Zr) configurations as promising thermoelectric materials

Abstract: Interest in the application of thermoelectric devices for renewable energy has risen over the past decade. In this paper, we calculate the transport properties of various configurations of the transition metal dichalcogenide (TMD) MSe 2 (M = Hf, Zr, Ti) in search of promising thermoelectric materials at low/high temperatures. We explore the properties of the pure monolayer at discrete levels of biaxial tensile strain ( = 0%, 2%, 4%, 8%), as well as those of the van der Waals heterobilayers MSe 2 /MSe 2 using f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…For metallic TMDs, the thermal transport properties of TiSe 2 , TaSe 2 , and NbSe 2 were also computed. 19,24,25 κ ph of these metallic TMDs was found to be one to four orders of magnitude lower than that of silicene 26 and graphene. 27 However, these studies did not consider the contribution of the electronic thermal conductivity (κ e ) component which actually has been recently demonstrated to be significant in e-doped 2D berylonitrene 28 and metallic 2D carbon allotropes.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…For metallic TMDs, the thermal transport properties of TiSe 2 , TaSe 2 , and NbSe 2 were also computed. 19,24,25 κ ph of these metallic TMDs was found to be one to four orders of magnitude lower than that of silicene 26 and graphene. 27 However, these studies did not consider the contribution of the electronic thermal conductivity (κ e ) component which actually has been recently demonstrated to be significant in e-doped 2D berylonitrene 28 and metallic 2D carbon allotropes.…”
mentioning
confidence: 82%
“…18 The potential TMD for applications brings into focus their thermal transport properties. In semiconducting MX 2 , the phonon transport properties of M = Mo, W, Zr, and Hf and X = S and Se have been extensively studied using first-principlesbased methods [19][20][21][22][23] that predict κ ph based on only threephonon (3ph) scattering events. An overview of these studies reveals that the phonon-dominated thermal conductivity κ ph in octahedral (1T)-type TMDs is much lower than that in trigonal prismatic (2H)-type TMDs when the characteristic length of the materials is small (1 µm).…”
mentioning
confidence: 99%
“…As strain increases, the collective effect of the increase in PF and decrease in κ L leads to an improvement in p-and n-type ZT up to 2.47 and 1.91 respec-tively, at room temperature 196 . In another study 197 , adopting the κ L values from a previously reported results 62,198 , the strong influence of strain on ZT values was also depicted for TiSe 2 via BoltzTraP2 calculations.…”
Section: Theoretical and Experimental Studies On Thermoelectric Prope...mentioning
confidence: 83%
“…The room temperature ZT values of these multilayers were calculated as 3.83 and 1.84 for HfSe 2 and ZrSe 2 , respectively. TE coefficients of van der Waals heterobilayers consists of HfSe 2 /TiSe 2 , ZrSe 2 /HfSe 2 and ZrSe 2 /TiSe 2 combinations are also investigated using BoltzTraP2 tool 197 . ZT values are estimated via previously reported κ L values 62,198 .…”
Section: Theoretical and Experimental Studies On Thermoelectric Prope...mentioning
confidence: 99%
“…[1][2][3] In this context, people can gradually reduce their dependence on traditional fossil energy by developing renewable and clean energy. [4,5] At present, the main renewable clean energy devices are solar cells, wind-driven generators, hydroelectric generators, and thermoelectric (TE) devices. [6,7] Among these kinds of energy conversion technologies, TE materials can not only be used in power generation devices, but also be used in integrated circuits by making solid-state cooling systems.…”
Section: Introductionmentioning
confidence: 99%